The Role of AI, Filter Bubbles, and Echo Chambers in Political and Religious Polarization on Social Media - Zabieno, Anggeline Saviola; Damayanti, Damayanti; Abdullah, Ahmad Zaki (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
This research is motivated by the existence of AI, filter bubbles, and echo chambers, which narrow the scope of interaction and isolate users from diverse perspectives. In Indonesia, politicians often use religion as a political tool, which further exacerbates the situation. This research aims to understand how the interaction between AI, filter bubbles, and echo chambers impacts political and religious polarization on social media. This study employed a qualitative approach, utilizing a literature review method that analyzed relevant journal articles. The results indicate that political and religious polarization occurs when society is divided into groups with increasingly divergent views and values, thereby exacerbating social tensions and widening the gap between these groups. AI makes extreme political content more likely to be shared than moderate information. Filter bubbles limit exposure to differing views and reinforce confirmation bias. The echo chamber exacerbates polarization by encouraging individuals to interact only with those who share their beliefs. Individuals or groups vulnerable to polarization are those who have difficulty accepting new information, only consume content that aligns with their beliefs, perceive other groups as being unobjective or biased, and have low digital awareness and literacy. The principle of Islamic brotherhood can help mitigate political and religious polarization by teaching the importance of mutual respect for differences and maintaining harmony among Muslims.